Edukasi Pedoman Gizi Seimbang dan Implementasi Isi Piring Makanku pada Siswa SMP Negeri 5 Kota Jambi - Aisah Aisah; Aidil Havis (Jurnal Abdimas Kesehatan (JAK), 2023)
Knowledge of nutrition is one of the indirect causes of malnutrition. Increasing knowledge through nutrition education can prevent malnutrition and improve a person's behavior to consume food according to their nutritional needs. Good knowledge is one of the factors that influence a person's attitude and behavior. Health promotion activities are carried out to provide knowledge about health and ultimately to prevent health problems. The purpose of community service activities is to provide or increase knowledge and understanding of students of SMP Negeri 5 Jambi City regarding guidelines for balanced nutrition and the implementation of the contents of my eat plate. Counseling is an effort to change human behavior through an educative approach. Based on the results of an initial survey conducted at SMP Negeri 5 Jambi City in Juli 2022, it was found that students' functional nutritional literacy regarding balanced nutrition was still low. Only 19% of students who have good functional nutritional literacy. The solution offered is nutrition education about balanced nutrition guidelines that can increase students' knowledge and implementation of "the contents of my dinner plate" to address nutritional problems in SMP Negeri 5 Jambi City students.. The implementation of this education was carried out in a friendly manner using leaflet media and power points. Before and after the education, an evaluation of the participants' knowledge and attitudes regarding balanced nutrition guidelines was carried out through a pretest and posttest using a questionnaire. experienced an increase, where the results of the pre-test knowledge were less than 15 students and the results of the post-test were 3 students, while the pre-test results of good knowledge were 7 students and the results of the post-test were 20 students.